Virological and epidemiological analysis of coxsackievirus A24 variant epidemic of acute hemorrhagic conjunctivitis in Okinawa, Japan, in 2011 - Harada K; Fujimoto T; Asato Y; Uchio E (Clinical Ophthalmology, 2015)
Kazuhiro Harada,1 Tsuguto Fujimoto,2 Yoshimori Asato,3 Eiichi Uchio1 1Department of Ophthalmology, Fukuoka University School of Medicine, Fukuoka, 2Infectious Disease Surveillance Center, National Institute of Infectious Disease, Tokyo, 3Asato Eye Clinic, Itoman, Japan Background: Acute hemorrhagic conjunctivitis (AHC) is a highly contagious enterovirus infection of the conjunctiva and cornea. Coxsackievirus A24 variant (CA24v) is one of its etiological agents. We report a clinical, epidemiological, and virological analysis of a large epidemic of AHC that occurred from May to September, 2011, in Okinawa, Japan.Methods: Clinical and epidemic aspects were evaluated for 435 AHC patients (348 bilateral and 87 unilateral, 783 eyes). Virological studies were carried out on nine isolates from ten patients. Virus isolation and direct detection of the enterovirus genome by the reverse transcription polymerase chain reaction method and complete nucleotide sequencing of the VP1 gene and phylogeny-based classification using the VP4 sequences were carried out.Results: The 11–15-year age group comprised the highest (62.0%) proportion of cases among all age groups. Conjunctival hyperemia was present in all patients, and subconjunctival hemorrhage, superficial punctate keratitis, and preauricular lymphadenopathy were present in 25.4%, 10.3%, and 7.8% of eyes, respectively. CA24v was isolated from the epidemic strain, and phylogenetic analysis based on a fragment of the VP1 gene showed 96%–97% identity between the current strain and the recent China/GD01/2010 strain.Conclusion: These findings demonstrate that the clinical and epidemiological features of AHC observed in this study were similar to those of the past epidemic in the same region. It should be noted that sequential outbreaks of AHC due to CA24v might occur in the same location after a considerable period of time, and public health precautions are necessary to control this explosive epidemic. Keywords: enterovirus, coxsackievirus, acute hemorrhagic conjunctivitis, polymerase chain reaction, epidemiology